Prospect of Sustainable Tourism Development In Sikka Regency, East Nusa Tenggara Province - Richardus Muga; Michael Rudolfus Sawu (Cita Konsultindo Research Center, 2024)
This article aims to propose a sustainable tourism development approach to promote social change within the scope of regional tourism. The research seeks to analyze regional tourism development policies, the social impact of regional tourism development, and to generate a sustainable tourism approach as a panacea for addressing the ethical challenges of regional tourism development. This research offers a holistic perspective on social changes in regional tourism, envisioning a future full of promise. The research methodology employed is qualitative, using a verificative approach. Data collection techniques include observation, in-depth interviews, documentation, and literature review. This article finds that regional tourism development policies are not well-targeted, lacking in destination planning, insufficiently involving local communities, and resulting in minimal social impact on the local population. This article contributes to the proposed theoretical model for analyzing the sustainability perspective of regional tourism in Sikka Regency, concerning future development directions within the context of sustainable tourism.